2016
DOI: 10.12681/scad.9976
|View full text |Cite
|
Sign up to set email alerts
|

Confronting homelessness in Greece during at time of crisis

Abstract: <p>This article attempts to examine the policies for confronting homelessness in Greece during the crisis. The thesis proposed is that, regardless of the signs of a significant deterioration in the problem of homelessness, a range of policies has been developed that focus on the management of its most extreme and publicly visible manifestations. Social interventions are inadequate, fragmented, repressive in their nature, and with a strong emphasis on charity. This can be seen in the emphasis given to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
6
0
2
Order By: Relevance
“…Skamnakis (2016) investigating local childcare policies in Greece found that they have a residual character and fail systematically to meet demand. A similar observation was made by Kourachanis (2016) in relation to homelessness policies, begging the question if these are actually having a positive impact or simply recycling an extreme social problem. Finally, the persistent reliance of these projects in EU Funds and donations raises several concerns about their sustainability and employment conditions (Petmesidou, 2013).…”
Section: The New Trajectory Of Social Policy In Greece: Current Debatessupporting
confidence: 58%
See 1 more Smart Citation
“…Skamnakis (2016) investigating local childcare policies in Greece found that they have a residual character and fail systematically to meet demand. A similar observation was made by Kourachanis (2016) in relation to homelessness policies, begging the question if these are actually having a positive impact or simply recycling an extreme social problem. Finally, the persistent reliance of these projects in EU Funds and donations raises several concerns about their sustainability and employment conditions (Petmesidou, 2013).…”
Section: The New Trajectory Of Social Policy In Greece: Current Debatessupporting
confidence: 58%
“…While these projects initially emerged as a frontline response to crisis, they have gradually been consolidated and become the norm in the field of social protection in the country. Despite this, to present, little is known as to their effectiveness to reduce AROPE, with the results of existing studies suggesting that they are limited both in terms of nature and scope (Skamnakis and Pantazopoulos, 2014;Skamnakis, 2016;Kourachanis, 2016). This paper probes these findings through surveying beneficiaries of one of the most widely implemented projects in a case study in the municipality of Pavlos Melas.…”
Section: Introductionmentioning
confidence: 98%
“…These indirect signs give rise to the suspicion that there was an increase in the homeless population, a claim that has been confirmed by small-scale count efforts carried out by local authorities and NGOs (Arapoglou and Gounis, 2015; Kourachanis, 2015). Based on the above reports, there are strong indications that housing shortages during the crisis have been changing and moving in a negative direction.…”
Section: Homelessness Policies In Portugal and Greecementioning
confidence: 95%
“…Similarly, the phenomenon of homelessness had hardly been addressed before the crisis. The lack of government policies targeting the homeless led to the development of a fragmented and piecemeal network of protection for this population group, with the involvement of the Church, local authorities and NGOs (Kourachanis, ).…”
Section: The Notion Of Solidarity and The Greek Casementioning
confidence: 99%
“…Against this backdrop, the emergence of “neo‐homeless” individuals, that is people who before the crisis enjoyed decent living conditions and had a satisfactory level of education, is unsurprising (Kourachanis, ). The new pattern of homelessness reflects the combination of higher levels of qualifications and work experience with a reduced ability to meet housing costs (FEANTSA, ).…”
Section: The Notion Of Solidarity and The Greek Casementioning
confidence: 99%